THE IMPLEMENTATION OF MULTICULTURAL ISLAMIC EDUCATION VALUES IN LEARNING ISLAMIC RELIGIOUS EDUCATION (PAI) IN SCHOOL - Khoirul Anwar (Universitas Islam Malang, 2021)
This article is the result of research conducted at two multicultural elementary schools with multi-religious students and teachers. This research was intended to determine the value of multicultural education and the implementation of these values in Islamic religious education learning. This research utilized a qualitative approach with the type of case study. The data in this research were successfully gathered by means of observation, in-depth interview, and interpretation of related documents. Furthermore, the data in this research were then analyzed by using Robert K Yin’s case analysis which contains five phases of analysis, specifically: (1) Compiling, (2) Disassembling, (3) Reassembling (and Arraying), (4) Interpreting, and (5) Concluding. Subsequently, a cross-site analysis was carried out by comparing and combining the findings obtained from each site. The research results showed that the values of multicultural Islamic education in PAI learning were successfully implemented by teachers through several stages, including: First; integrated multicultural values in the school’s vision, mission, and goals, PAI Syllabus, and PAI Lesson Plans. Second; conducted learning process by using additive, transformative and social action approaches. Third; utilized democratic learning method by using various learning strategies such as dialogue, simulation and role playing, applied exemplary method, and mudzakaroh method. Fourth; evaluated the learning process by covering three assessment domains, particularly cognitive domain, affective domain, and skill domain. Fifth; practiced learning multicultural values in religious activities and social activities held by the school.Keywords : Implementation, Multicultural values, Islamic education learning